Risks and Opportunities of Artificial Intelligence Integration in Rural Hospital Entrepreneurship: Perspectives from Healthcare Practitioners (JMMR (Jurnal Medicoeticolegal dan Manajemen Rumah Sakit), 2025)
Artificial Intelligence (AI) has become a key innovation in improving healthcare service quality and efficiency; however, its adoption in rural hospitals presents both opportunities and challenges. This study aims to explore the integration of AI in hospital entrepreneurship within Wonogiri, Central Java, to identify its benefits and risks in a rural context. A qualitative approach was employed through in-depth interviews with seven healthcare practitioners, including hospital and clinic owners or directors. Data were transcribed, coded, and thematically analyzed to obtain comprehensive insights. The findings revealed that AI offers several opportunities, including reducing operational costs, enhancing patient adherence through automated reminders, improving efficiency in human resource management, and optimizing inventory systems. Nevertheless, notable risks include patients' limited technological readiness, the low digital competence of healthcare staff, infrastructure and maintenance challenges, and high initial investment costs. This study makes a unique contribution by presenting an in-depth examination of AI implementation in rural healthcare entrepreneurship—an area that has been rarely examined in prior studies. The results provide both academic insight and practical guidance for hospital managers and policymakers in balancing technological innovation with local constraints to support inclusive digital transformation.